Relationship between insulin-like growth factor-1 and cerebral small vessel disease and its mechanisms: advances in the field - Du, Hao; Xia, Jian; Huang, Lei; Zheng, Lan; Gu, Wenping; Yi, Fang (Frontiers in Aging Neuroscience, 2023)
Insulin-like growth factor-1 (IGF-1) is an active polypeptide protein that closely resembles the structural sequence of insulin and is involved in a variety of metabolic processes in the body. Decreased IGF-1 circulation levels are associated with an increased risk of stroke and a poorer prognosis, but the relationship with cerebral small vessel disease (cSVD) is unclear. Some studies found that the level of IGF-1 in patients with cSVD was significantly reduced, but the clinical significance and underlying mechanisms are unknown. This article reviews the correlation between IGF-1 and cerebrovascular disease and explores the potential relationship and mechanism between IGF-1 and cSVD.